PENDAMPINGAN PENCIPTAAN MURAL MELALUI METODE SERVICE-LEARNING DI SEKOLAH DASAR NEGERI 010 CIDADAP-BANDUNG - Ariesa Pandanwangi; Belinda Sukapura Dewi; Carla Angelica (LPPM Universitas Bina Bangsa, 2024)
This community service aims to increase creativity through making murals made using service-learning methods at Sekolah Dasar Negeri (SDN) 010 Cidadap, Bandung. The service-learning method is implemented as a learning approach that involves students in the mural making process, while also making a positive contribution in the form of knowledge transfer to school students. The service learning (SL) method with active participation of students is used in this service. Structured steps are taken to design and implement the program, as well as the management of collaborative activities between students, teachers, lecturers and the community. Evaluations were conducted to measure the impact of this dedication, including improving art skills and creativity, as well as positive responses from students, teachers, and the community to the creation of murals. The results show that this method of teaching through service has succeeded in improving students' artistic skills and creativity in wall processing through making murals. This activity also strengthens the relationship between Maranatha Christian University, the school, social community, society, and industry. The practical implication of this service is the development of a learning model based on community service to increase student creativity and competence in the arts while improving the learning process of students outside the campus through community service activities